2011
DOI: 10.1002/ibd.21604
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Crohnʼs disease perceived work disability questionnaire

Abstract: The CPWDQ seems to be a valid, reliable tool for measuring subjective work disability in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…Additional details from these studies are provided to supplement the descriptions of concepts elicited from study participants (Table 2). The 6 most widely used and established IBD-specific health-related quality of life measures 9 were reviewed: the Inflammatory Bowel Disease (IBDQ) 6 Questionnaire, a 36-item version of the IBDQ 33 , the Crohn’s Disease Perceived Work Disability Questionnaire(CDPWDG) 34 , the Inflammatory Bowel Disease Stress Index (IBDSI) 8 , the Rating Form of IBD Patient Concerns (RFIPC 7 , and the Work Productivity and Activity Impairment Questionnaire: Crohn’s Disease (WPAI-CD) 35 . Concepts captured by items in the IBD-specific PRO measures were added to those identified by the focus groups, interviews, and qualitative studies in the literature to produce an inventory of all concepts identified by each of these 3 sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional details from these studies are provided to supplement the descriptions of concepts elicited from study participants (Table 2). The 6 most widely used and established IBD-specific health-related quality of life measures 9 were reviewed: the Inflammatory Bowel Disease (IBDQ) 6 Questionnaire, a 36-item version of the IBDQ 33 , the Crohn’s Disease Perceived Work Disability Questionnaire(CDPWDG) 34 , the Inflammatory Bowel Disease Stress Index (IBDSI) 8 , the Rating Form of IBD Patient Concerns (RFIPC 7 , and the Work Productivity and Activity Impairment Questionnaire: Crohn’s Disease (WPAI-CD) 35 . Concepts captured by items in the IBD-specific PRO measures were added to those identified by the focus groups, interviews, and qualitative studies in the literature to produce an inventory of all concepts identified by each of these 3 sources.…”
Section: Resultsmentioning
confidence: 99%
“… a CDPWDG: Crohn’s Disease Perceived Work Disability Questionnaire 34 IBDQ: Inflammatory Bowel Disease Questionnaire (32 items) 6 IBDQ-36: Inflammatory Bowel Disease Questionnaire (36 items) 33 IBDSI: Inflammatory Bowel Disease Stress Index 8 RFIPC: Rating Form of IBD Patient Concerns 7 WPAI-CD: Work Productivity and Activity Impairment Questionnaire: Crohn’s Disease 35 …”
Section: Figurementioning
confidence: 99%
“…The PROM characteristics such as the provided construct definitions, target populations, subscales, and range of scores are represented in Table 1 . Of all 44 instruments seven report to measure some concept of disability: two on perceived work disability 39 , 40 and the rest on a form of disease-related disability. 41–45 Eighteen PROMs could be categorised as measuring self-reported disease activity.…”
Section: Resultsmentioning
confidence: 99%
“…For six PROMs it was not clear how many subscales were present or which items made up the reported subscales. 39–41 , 44 ,67,78 The reported content validity studies represent the instruments as a whole. Comprehensibility was the most studied [ n = 17] aspect of content validity, including five on the IBDQ-32 [and modifications] and one on the IBDDI-14-s, aimed at testing an adaptation in a new language.…”
Section: Resultsmentioning
confidence: 99%
“…The psychometric properties of the UC-WDQ were evaluated. [ 12 ] The UC-WDQ's convergent validity was established by correlating its scores with disease activity (measured by the Mayo index and days of hospitalization) and QoL (measured by the IBDQ-9 and the EuroQol-5D). Discriminant validity was measured by comparing the UC-WDQ scores in patients with active vs inactive UC, hospitalized vs not hospitalized in the previous year, and patients who had needed sick leave vs those who had not, also in the previous year.…”
Section: Methodsmentioning
confidence: 99%